Effectiveness of video assisted teaching on knowledge, attitude and practice among primary caregivers of children with Autism Spectrum Disorder. Issue 4 (9th May 2019) - Chandran, Hena; Jayanthi, K.; Prabavathy, S.; Renuka, K.; Bhargavan, Rajesh
Abstract : Purpose: Parents or primary caregivers of children with Autism Spectrum Disorder (ASD) have important role in early recognition of the disorder as well as in the management of the disorder. Knowledge, attitude and practice of primary caregivers towards children with ASD are important factors in promoting health and wellness of such children. The purpose of this paper is to evaluate the effectiveness of video-assisted teaching regarding care of children with ASD on knowledge, attitude and practice among primary caregivers. Design/methodology/approach: Quasi-experimental research design with one group pre-test post-test was adopted. A total of 60 primary caregivers were selected through stratified random sampling technique. Video-assisted teaching was given to 60 primary caregivers. Data collection was done before and after the video-assisted teaching programme using structured questionnaire which consists of 57 questions. Findings: The result of the study showed that the post-test level of knowledge attitude and practice among primary caregivers of children with ASD was significantly high ( p <0.0001) when compared to pre-test level by using Wilcoxon Signed Rank Test. The study finding revealed that video-assisted teaching was effective in enhancing the knowledge, developing a positive attitude and good practice among primary caregivers regarding care of children with ASD. Social implications: Findings of this study will help mental health nurses, psychologists, intellectual disability nurses, teachers, public health, social workers, etc. to know the importance of video-assisted teaching programme regarding care of children with ASD and to motivate the primary caregivers to participate in such teaching programme. The community mental health nurse can plan video-assisted teaching programme in a community regarding care of children with ASD. Originality/value: Results of this study indicate that the video-assisted teaching is effective and helps the primary caregivers to enhance the knowledge, attitude and practice regarding care of children with ASD. So continuous awareness in primary health centre and community area is necessary to improve the knowledge, attitude and practice of primary caregivers.